Enforcement procedure on unregistered real estate ownership right - Petrović Stojana (Zbornik Radova Pravnog Fakulteta u Nišu)
According to the real estate laws applicable in the entities of Bosnia and Herzegovina, the failure of the debtor to register his/her right of ownership on real estate is not an obstacle to instigating the enforcement procedure. However, given the fact that the registration of the enforcement debtor's ownership right on immovable property is a precondition for enforcement proceedings, the current procedural rules cannot be considered an adequate normative response of domestic legislators to the enforcement creditor's right to settle, especially when the debtor has no other assets that could be offered for settlement. In this paper, using the legal science methodology, the author discusses and evaluates the axiological value of the legislative solutions on the issue of instituting the enforcement procedure against the debtor whose real estate right has not been registered. The analysis includes both domestic law and laws of selected neighbouring countries. The author examines two situations: 1) when the registration of the ownership rights has a constitutive effect, and 2) when the effect on the debtors acquisition of right is only declarative. The author concludes that the temporal correlation between the moment of rendering a decision to initiate the enforcement procedure on debtor's unregistered immovable property and the moment of registration of the debtor's ownership right is determined by at least three possible legislative models on enforcement. Each of the observed models of creditor's forced settlement which are conditioned by the prior registration of the debtor's real estate ownership right may be improved. The author proposes two possible ways: to make the procedure for acquiring the legal ground for the registration of the debtor's ownership right more efficient; or, in case it is not possible, to enable the creditor to make an inventory of the seized debtor's immovable property.